An alternative norm of intention consistency. (6th April 2020) - Núñez, Carlos
Abstract: In this paper, I formulate a norm of intention consistency that is immune to the kind of cases that have been put forth to argue either that rationality does not require consistency between an agent's intentions, or that, if it does, then rationality is not normative. The norm I formulate mimics refinements that have been made to the norm of means‐end coherence in response to cases where, intuitively, you need not be irrational when you intend an end e, despite not intending the means m you believe to be necessary for e, because you do not believe that intending m is necessary for e . Similarly, according to the norm I put forth, if you intend e, and believe that e is inconsistent with e*, you need not be irrational if you also intend e*, as long as you do not believe that intending e* is inconsistent with e .